The tortured poets department the anthology - Swift, Taylor 1989- (Hal Leonard, 2023)
You've memorized all the songs from the double album, now it's time to play them for yourself! Our matching folio to The Tortured Poets Department: The Anthology features all 31 tracks meticulously arranged for piano and voice with guitar chord frames. Dive into the emotional depth of Swift's music and play along with your favorite tracks from "Fortnight" to "The Manuscript," to "So Long, London" to "So High School," and all the others. Immerse yourself in the storytelling prowess of Taylor Swift and bring her songs to life with your own unique voice and talent!
Songs from Taylor Swift's 2024 recording by the same title
For voice and piano, with symbols and guitar chord diagrams
Words and music written or co-written by Taylor Swift
"Universal Music Publishing Group"--Back cover
"Piano/Vocal/Guitar"--Cover
Keywords: Popular music / 2021-2030; Rock music / 2021-2030; Popular music / Vocal scores with piano; Popular music / Vocal scores with guitar; Songs with piano; Songs with guitar; Folk-rock music; Chansons acc. de piano; Chansons acc. de guitare; Folk-rock; Popular music; Songs; Scores; Arrangements (Music); Notated music; Musique populaire; Partitions (Musique); Arrangements (Musique); Musique notée